An Analysis of Industry and Sector-Specific Impacts of a Japan-Philippines Economic Partnership - Royce Elvin O. Escolar (Philippine Institute for Development Studies (PIDS), 2004)
The paper aims to identify industry and macrolevel factors that affect competitiveness of selected sectors upon the implementation of the JPEPA. Priority sectors identified by the Department of Trade and Industry, accounting for 82% of total Philippine exports to Japan in 2002, were included in the study. For Philippine industries to gain, market access issues on trade facilitation, nontariff barriers and recognition of standards come into play especially for the service and agricultural sectors. Internal industry-level factors deal with access to raw materials, lowering input costs through growth of support industries and infrastructure development, SME financing, exploiting economies of scale, firm-level flexibility in part due to utilization of new technologies, greater knowledge of the Japanese market and sustainability of human capital competitiveness through training. Social safety nets, if required, may be more effective if they focus on retraining and relocation of displaced workers. Cement, the import competing industry identified in the paper, will only face limited competition due to the constrained capacity and market of the Japanese cement importer. Industry-level competition or triangular relations with complementary counterparts in ASEAN countries to serve the Japanese market should be explored especially given that an ASEAN-Japan FTA is also being negotiated. The main macrolevel factor is on poor governance leading to political and economic uncertainty which adversely affect the attractiveness of the country as an investment site.
Keywords: 330; bilateral agreements; industry study; sector competitiveness; market access; safety nets; Japan-Philippines economic partnership; Wirtschaftsstruktur; Freihandelszone; Philippinen; Japan